2013
DOI: 10.1038/pr.2013.54
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical choline and related methylamines betaine and dimethylglycine in relation to birth weight

Abstract: Background: Low birth weight (LBW) is associated with increased morbidity and mortality for the newborn and risk of chronic disease in adulthood. Choline plays an essential role in the integrity of cell membranes, methylation reactions, and memory development. We examined whether choline, betaine, and dimethylglycine (DMG) concentrations were associated with LBW in Dutch women. Methods: Blood was sampled from umbilical cords (UCs) at delivery in singleton pregnancies (n = 1,126). Maternal blood was sampled at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 28 publications
4
25
1
Order By: Relevance
“…Despite the lack of significance, the strong correlations for vitamin B6 and iron are of interest given their importance in preeclampsia, birth weight, neuromotor development, and maternal anemia in pregnancy [21, 23]. Betaine is a relatively new methyl-nutrient being explored and thus the exact role of betaine during pregnancy is unclear, however it also appears to be important for fetal development, birth weight, and early brain development [28, 73]. …”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of significance, the strong correlations for vitamin B6 and iron are of interest given their importance in preeclampsia, birth weight, neuromotor development, and maternal anemia in pregnancy [21, 23]. Betaine is a relatively new methyl-nutrient being explored and thus the exact role of betaine during pregnancy is unclear, however it also appears to be important for fetal development, birth weight, and early brain development [28, 73]. …”
Section: Discussionmentioning
confidence: 99%
“…Increased DMG has been correlated with higher birth weight, in a LBW vs normal weight cohort, due to alterations in choline metabolism. 63 Moreover, it has been suggested that alterations in methionine metabolism could impact on purine and pyrimidine metabolism, deoxyribonucleic acid (DNA) synthesis and/or cell proliferation, and affect fetal growth. 64 This is consistent with the noted disturbances in the tryptophannicotinamide adenine dinucleotide (tryptophan-NAD + ) pathway ( Figure 6) and the significant intensity decrease of purines/pyrimidines resonances at δ 6.0−6.5.…”
Section: Prematurity and Comparison To Other Disordersmentioning
confidence: 99%
“…Methionine, also an essential amino acid, is particularly important during fetal development because of high demands for protein synthesis (18) . To date, only three epidemiologic studies have explored the association of maternal circulating choline and betaine with birth weight, and the results have been inconsistent (19)(20)(21) . While a large mother-offspring cohort reported an inverse association between maternal plasma betaine and birth characteristics included, that is, birth weight or birth length or abdominal fat mass (19) , other studies reported null association between either biomarkers and birth weight (20,21) .…”
mentioning
confidence: 99%